Implementasi Penggunaan Media Baamboozle untuk Meningkatkan Motivasi Belajar Matematika Kelas 4 SDN 11 Panai Hulu - Shiddiq, Imam; Sari, Mawar; Nasution, Zahira Andryani; Purba, Hasnah Nurhayati; Kurniati, Alya; Junitri, Anisa; Yanti, Nelmida; Rahayu, Dwi; Wulandari, Anggi; Lubis, Bunga Puspita; Herpasyah, Febyna; Putri, Rahma Eka; Puspita, Adinda Dara; Andini, Nanda Dwi; Yulianti, Dina; Syahputri, Hemalia (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to improve the mathematics learning outcomes of grade IV students of SDN 11 Panai Hulu by using Baamboozle. This research is a Classroom Action Research (PTK). The research is carried out in two cycles, where each cycle consists of planning, implementation, observation, and reflection. In each cycle, the Project Based Learning (PjBL) learning model supported by Baamboozle was used to show a significant improvement in student learning outcomes. The results of the analysis showed that the average student score increased from 77.25% in the first cycle to 84.97% in the second cycle, with the percentage of learning completion also increasing significantly. The use of Baamboozle as a learning aid allows students to collaborate, compete, and interact in a fun atmosphere, thereby improving their understanding of the math material. This study concludes that digital educational game-based learning methods, such as Baamboozle, are effective in improving student learning outcomes, as well as providing a more interesting and interactive learning experience. Recommendations are given so that this method is more often applied in the learning process in elementary schools to improve the quality of education.